Evaluation as a Tool for Developing the Quality of the Academic Libraries. Case Study at a Large and Traditional Research Oriented Scandinavian University - Viewpoint of a Member of the Evaluation Panel - Sahlin, Gunnar (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
We were invited as an international review team to assess the development of the library system in the Helsinki University. As reviewers and experts we came to Helsinki for two days in May 2004 - Hans Geleijnse from The Netherlands, Sinikka Koskiala from Finland and myself from Sweden. The result of our evaluation is the report Follow-up Evaluation of Library and information Services in Helsinki University 2004 (Geleijnse, Koskiala & Sahlin, 2004).